Diseño de proceso y propuesta de mejoramiento al programa semillero de investigadores de la ESPAM MFL - Intriago Chica, Anny Selena (2021)
The present investigation was oriented to the design of processes and proposals for improvement to the Researchers Seed Program (PSI) at Escuela Superior Politécnica Agropecuaria de Manabí “Manuel Félix López” (ESPAM MFL), with the aim of strengthening the research activity of the students undergraduate. The methodology was initially based on observation and interview techniques, the instructions for the elaboration of the institution's process manuals were used for the design of the flowcharts and process files of the PSI sub-processes, and the Added Value Analysis was also applied (AVA) to detect the shortcomings that existed in the different procedures and activities studied. Finally, it was concluded that it is necessary for the institution to establish a relevant quality management system in its institutional processes to reduce the weaknesses found in each of them, likewise, that constant evaluations be carried out on the PSI processes, since this contributes in a positive way to the university community in relation to scientific research. Subsequently, the improvement proposal was elaborated, which was socialized with the personnel of the General Research Coordination (CGI), to explain the level of efficiency that was managed to increase in each sub-process studied.